Switching tenofovir disoproxil fumarate to tenofovir alafenamide in a real life setting: what are the implications?. Issue 6 (17th February 2020) - Schwarze‐Zander, C; Piduhn, H; Boesecke, C; Schlabe, S; Stoffel‐Wagner, B; Wasmuth, JC; Strassburg, CP; Rockstroh, JK
Abstract : Objectives: Development of novel antiretrovirals aims at reducing long‐term toxicities. Tenofovir disoproxil fumarate (TDF) has been associated with potential nephrotoxicity. The aim of our study was to assess the impact of switching from TDF to tenofovir alafenamide (TAF) on functional nephropathy and lipid parameters in a real‐life setting. Methods: We retrospectively analysed data from 347 HIV‐infected patients switching from a TDF‐ to a TAF‐containing regimen between April and December 2016. Sociodemographic, clinical and laboratory data were collected at TDF‐to‐TAF switch, and at 3 and 6 months thereafter. Proteinuria and albuminuria were classified according to Kidney Diseases Improving Global Outcomes (KDIGO) guidelines. Results: At time of switch, moderately and severely increased proteinuria was detected in 32% and 8% of patients, respectively; however, urine dipstick analysis was negative in 84% and 42%, respectively. Moderately and severely increased albuminuria was found in 17% and 3% of patients, respectively. In patients with a urinary protein‐to‐creatinine ratio (UPCR) ≥ 150 mg/g, the mean value declined from 416 mg/g at baseline to 272 mg/g ( P < 0.001) and 242 mg/g ( P < 0.001) after 3 and 6 months, respectively. Patients with an albumin‐to‐creatinine ratio (UACR) ≥ 30 mg/g showed no significant decrease of albuminuria. Mean total cholesterol increased from 187 mg/dL at baseline to 202 ( P < 0.001) and 208 mg/dL ( P < 0.001) at 3 and 6 months, respectively, and mean low‐density lipoprotein (LDL) cholesterol increased from 114 mg/dL at baseline to 124 ( P < 0.001) and 128 mg/dL ( P < 0.001), respectively. As mean high‐density lipoprotein (HDL) cholesterol increased from 50 mg/dL at baseline to 54 ( P < 0.001) and 57 mg/dL ( P < 0.001) at 3 and 6 months, respectively, the LDL:HDL ratio remained stable. Conclusions: In an aging HIV‐infected cohort, proteinuria and albuminuria were common findings and were underdiagnosed via urine dipstick. Our real‐life data suggest that laboratory markers of moderately/severely increased proteinuria improved after TDF‐to‐TAF‐switch. Lipid profiles were not aggravated. Long‐term follow‐up is needed to determine the clinical benefit of the TDF‐to‐TAF switch.